2008
DOI: 10.3354/ame01248
|View full text |Cite
|
Sign up to set email alerts
|

Tracing carbon and nitrogen incorporation and pathways in the microbial community of a photic subtidal sand

Abstract: The pathways and fate of C and N in the microbial compartment of a coastal permeable sandy sediment in the photic zone were studied in a pulse-chase experiment.13 C-bicarbonate and 15 N-nitrate were added to the water column on top of 5 sediment cores incubated in 4 transparent and 1 opaque laboratory chambers. After 9 h of labelling in the light and dark, stable isotope incorporation by microphytobenthos (MPB) and bacteria was quantified over a period of 4 d through the analysis of phospholipid-derived fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
4
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 75 publications
7
45
4
1
Order By: Relevance
“…BMA have also been shown to take up dissolved organic N directly (Nilsson & Sundback 1996). To complete the cycle, bacteria then recycled labeled BMA detritus and/or extrapolymeric substances exuded by the BMA (Smith & Underwood 1998, Veuger et al 2007a, Evrard et al 2008. Good agreement between bacterial and BMA fatty acids supports a tight coupling between these communities (r 2 = 0.93 and 0.92 for HIB and IWB, respectively), although bacteria have also been shown to recycle nutrients independent of BMA by reincorporating their own degradation products (Veuger et al 2006(Veuger et al , 2007a.…”
Section: Bacterial-bma Couplingmentioning
confidence: 99%
“…BMA have also been shown to take up dissolved organic N directly (Nilsson & Sundback 1996). To complete the cycle, bacteria then recycled labeled BMA detritus and/or extrapolymeric substances exuded by the BMA (Smith & Underwood 1998, Veuger et al 2007a, Evrard et al 2008. Good agreement between bacterial and BMA fatty acids supports a tight coupling between these communities (r 2 = 0.93 and 0.92 for HIB and IWB, respectively), although bacteria have also been shown to recycle nutrients independent of BMA by reincorporating their own degradation products (Veuger et al 2006(Veuger et al , 2007a.…”
Section: Bacterial-bma Couplingmentioning
confidence: 99%
“…To date, application of this technique in OMZ-impacted sediments has focused upon the fate of organic carbon, within shipboard incubations (for example, Woulds et al, 2007;Andersson et al, 2008;Moodley et al, 2011). The advent of a method to trace 15 N incorporation into hydrolysable amino acids (HAAs), including the bacteria-specific amino-acid D-alanine, (Veuger et al, , 2007b makes it possible to empirically assess bacterial N utilisation and de-coupling of C and N in marine sediments (Cook et al, 2007;Veuger and Middelburg, 2007;Evrard et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are only a limited number of studies that link in situ carbon flow from diatoms directly to heterotrophic microbes and also identify in detail the responsible microorganisms . Middelburg et al (2000) and Evrard et al (2008) have reported rapid transfer of carbon from microphytobenthos to bacterial biomass by combining in situ 13 C pulse-chase labeling and phospholipid-derived fatty acid (PLFA) biomarker analysis in order to differentiate between labeling in algae and heterotrophic bacteria. Previous studies suggested that EPS-derived carbohydrates were major intermediates in the transfer of organic matter between benthic diatoms and heterotrophic bacteria (Bellinger et al 2009;Oakes et al 2010;Taylor et al 2013).…”
mentioning
confidence: 99%